2017
DOI: 10.5114/hpr.2018.70357
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducational interventions to improve adolescents’ medical management of diabetes: A comprehensive review

Abstract: ). The increase in technologically assisted psychoeducational interventions using text, apps, and interactive Internet-based programming results in a qualitative update of psychoeducational interventions and program evaluations. Also noted is an increase in the number of family-focused interventions that have been evaluated and published. The results of the current comprehensive literature review yield 42 evaluative studies of psychoeducational interventions for adolescents with type 1 diabetes with mixed outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Using this strategy, 3 new studies were identified ( Hampson et al, 2001: 2 results ; Murphy et al, 2006: 1 result ). In addition, a reference list search performed on a recent comprehensive review of this literature ( Bergmame & Shaw, 2018 ) identified 7 new studies. After initial screening, 128 citations were retained for detailed screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this strategy, 3 new studies were identified ( Hampson et al, 2001: 2 results ; Murphy et al, 2006: 1 result ). In addition, a reference list search performed on a recent comprehensive review of this literature ( Bergmame & Shaw, 2018 ) identified 7 new studies. After initial screening, 128 citations were retained for detailed screening.…”
Section: Resultsmentioning
confidence: 99%
“…There is presently a large body of literature describing psychoeducational interventions for adolescents with T1D. However, comprehensive reviews of this literature have revealed mixed results in terms of intervention design and effectiveness ( Bergmame & Shaw, 2018 ; Hampson et al, 2001 ; Hendrieckx et al, 2020 ; Murphy et al, 2006 ). For example, Bergmame and Shaw ( 2018 ) identified 42 evaluative studies of psychoeducational interventions for adolescents with T1D published over the past 12 years.…”
Section: The Shortcomings Of Psychoeducational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation